Activated Hypothalamic Pituitary Adrenal Axis in Patients with Metabolic Syndrome - Kazakou, P.; Kyriazopoulou, V.; Michalaki, M.; Ierodiakonou, V.; Psyrogiannis, A.; Habeos, I. (Hormone and Metabolic Research, 2012)
Metabolic syndrome (MetS) is correlated with the activity of hypothalamic-pituitary-adrenal axis (HPA), but the underlying mechanism still remains elusive. The aim of this study was to investigate the HPA axis function in patients with MetS. This case-control study included 159 people. They were divided into 2 groups. The first group included 73 healthy volunteers (control group: 19 males, 54 females, mean±SD: 49.9±7.5 years old, with BMI: 27.9±4.42 kg/m2) and the second group included 86 patients with MetS (case group: 48 males, 38 females, mean±SD: 52.2±7.6 years old, with BMI: 30.5±5.35 kg/m2). An oral glucose tolerance test (OGTT) was performed for all subjects after a 12-h overnight fast, and blood samples were obtained for determination of ACTH, cortisol, insulin, C-peptide, and glucose levels. Serum cortisol after an overnight dexamethasone suppression test was determined in both groups. Patients with MetS had serum cortisol levels after an overnight dexamethasone suppression test significantly higher than controls. During OGTT plasma ACTH levels were higher at all time points in patients with MetS compared to controls, whereas serum cortisol levels were comparable between the 2 groups. Plasma ACTH during OGTT was also correlated with most of the components of MetS. The HPA axis in patients with MetS seems to be more active as evidenced by the higher cortisol levels after the overnight dexamethasone suppression test and by the higher ACTH levels during OGTT. This functional hypercortisolism might be involved in the pathogenesis of the metabolic syndrome.
Keywords: ACTH; cortisol; metabolic syndrome; glucocorticoids